Basic Issue of Child Sacrifice in The Abraham’s Trial: An Exegetical Study of Genesis 22:2 - Gosal, Fellix (Klabat Theological Review, 2022)
Abraham’s trial in Genesis 22 provokes inquiry into the matter of child sacrifice. The divine command in Genesis 22:3 consists of three imperatives that significantly contribute to a comprehensive understanding of the command. While the initial imperative designates Isaac as the direct object, the third imperative does not directly involve Isaac. Conversely, the employment of a chiastic structure emphasizes that the central focus of God’s command resides in the second imperative, which pertains to the journey towards the land revealed by God – an aspect intimately linked to the initial encounter between Abraham and God. Consequently, the command issued in Genesis 22 should not be interpreted within the framework of child sacrifice, but rather as a test of Abraham’s faith and a reaffirmation of God’s covenant with him and the Israelites. Keywords: child sacrifice, Abraham’s trial, covenant, promise son, promise land